Treatment of Anterior Cruciate Ligament Injury in Skeletally Immature Patients - Joshua L. Hudgens; Diane L. Dahm (Hindawi Limited, 2012)
The incidence of ACL tears is rising in the pediatric and adolescent populations as these individuals succumb to traumatic and nontraumatic athletic injuries. Management of this condition in the skeletally immature patient poses a challenge and is controversial. Operative reconstruction carries the concern for damage to the physis with resultant limb length inequality and angular joint deformity but provides stability to the knee and allows return of function in most patients. On the other hand, nonoperative treatment has been shown to carry an increased risk of meniscal and articular cartilage damage and is difficult from a compliance standpoint in this demographic. For the majority of skeletally immature patients, operative treatment is recommended as it has shown good clinical and functional results with minimal risk of growth disturbance. This paper aims to address the natural course of ACL injuries in the skeletally immature patient, treatment options with associated complications, and current preventative strategies.